On the reliability of the Old Testament - Kitchen, K. A. (Kenneth Anderson) (Grand Rapids, MI William B Eerdmans Publishing Company, 2003)
"Kitchen draws on a range of historical data from the ancient Near East - the Bible's own world - and uses it to reassess both the biblical record and the critics who condemn it. Working back from the latest periods (for which hard evidence is readily available) to the remotest times. Kitchen systematically shows up the many failures of favored arguments against the Bible and marshals pertinent permanent evidence from antiquity's inscriptions and artifacts to demonstrate the basic honesty of the Old Testament writers."--BOOK JACKET.
1. First things first -- What's in question? -- 2. "In medias res" -- the era of the Hebrew kingdoms -- 3. Home and away -- exile and return -- 4. The empire strikes back -- Saul, David, and Solomon -- 5. Humble beginnings -- around and in Canaan -- 6. Lotus eating and moving on -- Exodus and covenant -- 7. Founding fathers or fleeting phantoms -- the patriarchs -- 8. A vitamin supplement -- Prophets and prophecy -- 9. Back to Methuselah -- and well beyond -- 10. Last things last -- a few conclusions.
Includes bibliographical references (pages 501-601) and indexes.
Keywords: Bible. -- Evidences, authority, etc; Bible. -- History of Biblical events